Multibiometric systems and template security survey - Khalaf, Emad Taha; Norrozila, Sulaiman (JSRAD, 2015)
Multimodal biometric systems are capable of utilizing, more than one physiological or behavioral characteristic for enrolment either in verification or identification mode, It is generally believed that several biometric sources usually compensate for the weaknesses of single biometric fusion techniques. The features that extracted from the biometric samples considered a critical part of biometric system which is called biometric template it is one of the most crucial issues in designing a secure system.